Governance of the IMF : An Evaluation. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2008)
This paper assesses the degree to which the IMF governance is effective and efficient, and whether it provides sufficient accountability and channels for stakeholders to have their views heard. The focus is on institutional structures as well as on the formal and informal relationships between the IMF's main bodies of governance: the Executive Board, Management, and the International Monetary and Financial Committee. The evaluation highlights that for much of the past six decades, gradual reforms in its governance allowed the IMF to remain relevant in a changing world economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet